Hybrid Quinazoline 1, 3, 5‐Triazines as Epidermal Growth Factor Receptor (EGFR) Inhibitors with Anticancer Activity: Design, Synthesis, and Computational Study. (1st December 2020) - Pathak, Prateek; Rimac, Hrvoje; Grishina, Maria; Verma, Amita; Potemkin, Vladimir
Abstract: We report a series of hybrid quinazoline‐1, 3, 5‐triazine derivatives as EGFR inhibitors, which were synthesised and tested by using a variety of in vitro, in silico, and in vivo techniques. The derivatives were found to be active against different cancer cell lines and nontoxic against normal ones, with compounds 7 c, 7 d, 7 e, and 7 j being the most potent ones. The derivatives were also evaluated for angiogenesis inhibition potency in chicken eggs, and molecular docking and dynamics simulation studies were carried out to elucidate the fundamental substituent groups essential for their bioactivity. Additionally, a SAR study of the derivatives was performed for future compound optimisation. These studies suggested that the derivatives have a high affinity towards EGFR with favourable pharmacological properties. The most active compound (7 e ) was further evaluated for in vivo anticancer activity against DMBA‐induced tumours in female Sprague‐Dawley rats as well as its effects on plasma antioxidant status, biotransformation enzymes, and lipid profile. The study suggested that 7 e has lead properties against breast cancer and can serve as a starting compound for further development of anti‐EGFR compounds. Abstract : Different structure, similar efficiency : Hybrid quinazoline‐1, 3, 5‐triazine derivatives have been synthesised and tested for anticancer activity. Pharmacological evaluation indicated that substitution of the 1, 3, 5‐triazine ring by morpholine and aniline rings increases ligand potency in EGFR inhibition. In vivo evaluation showed that one compound based on a different scaffold has the potential to inhibit tumour growth through additional mechanisms of action.